Phased Fractional Low-Order Moment-Based Doppler Shift Estimation in the Presence of Interference Signals and Impulsive Noise - Bo Ni; Mengjia Wang; Jiacheng Zhang; Ying Zhang; Tao Liu (Fractal and Fractional)
Doppler shift estimation continues to be a critical challenge of utmost significance in both theoretical research and practical engineering applications. Many innovators have crafted solutions specific to this issue, with notable contributions across various signals and scenarios. Given that cyclostationary signals are prevalent in both artificial and natural phenomena, we propose a novel framework based on the phased fractional lower-order moment (PFLOM) for estimating Doppler shift in mixed cyclostationary signals. During the estimation process, a more realistic impulse noise model is examined in contrast to the ideal Gaussian noise typically assumed in conventional methods. This approach is meticulously derived through a series of detailed steps in line with cyclostationary signal processing and PFLOM principles. Furthermore, an extensive simulation has been conducted to validate the efficacy and robustness of our proposed method. It is anticipated that the concept and method presented here could be applied more broadly due to its solid theoretical underpinnings.